Interactions of chloroquine and/or ethanol on renal morphology of normal or low protein fed male sprague dawley rats - Abdulkadir, Abdurrahman (My University, 2018)
The aim of this study was to investigate the renal morphometric and histopathological changes, arising from the hazard of concurrent administration of chloroquine and alcohol on a background protein malnourished state using rat as experimental animal model. Sixty-four (64) rats were randomly distributed into eight groups of eight rats each as follows: control groups that received 0.9% saline and plain drinking water while on either normal or low protein diets (NPC, LPC). Chloroquine treatment groups while on either normal or low protein diets (NPQ, LPQ). Alcohol treatment groups while on either normal or low protein diets (NPE, LPE). Chloroquine and Alcohol treatment groups on normal or low protein diets (NPQE, LPQE). Chloroquine in 0.9% normal saline was administered once weekly to NPQ, LPQ, NPQE, and LPQE. While NPE, LPE, NPQE and LPQE received 6% ethanol in drinking water ad libitum. NPC and LPC received 0.9% normal saline and plain drinking water. After 8 weeks (60 days), the rats were terminated, kidneys were harvested and fixed for analyses. Routine H&E histology, Masson’s trichrome for collagen, kidney volume estimation, relative medullary thickness measurements, renal cortical thickness measurements, microscopic morphometry, glomeruli count and immunofluorescence for aquaporin 2 (AQP2) were conducted. Urine volume estimation, serum urea and creatinine were also assessed. The results showed a decreased mean body weight (p=0.0001), relative kidney weight (p=0.0001) and kidney volume (p=0.0001) in all low protein treated rats group compared to NPC and compared to their cohorts in normal protein group. The urine output decline with derangements of serum urea and creatinine in the low protein treated rats compared to NPC and compared to their cohorts in the normal protein group. There was upregulation of AQP2 water channel with increased collagen fibre deposition and distortion of normal renal histology in the experimental rat groups both within the normal protein and the low protein groups compared to NPC. In conclusion, concurrent administration of chloroquine and alcohol causes distortion of kidney histology and derangements of renal function in low protein fed rats and has the potential to cause kidney failure.
A Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfilment of the requirement for the degree of Master of Science in Medicine, Johannesburg 2018
Keywords: Chloroquine; Drug resistance